Evaluating the performance of clinical criteria for predicting mismatch repair gene mutations in Lynch syndrome: a comprehensive analysis of 3,671 families. - Steinke, V.; Holzapfel, S.; Loeffler, M.; Holinski-Feder, E.; Morak, M.; Schackert, H. K.; Gorgens, H.; Pox, C.; Royer-Pokora, B.; von Knebel-Doeberitz, M.; Buttner, R.; Propping, P.; et al. (Int J Cancer, 2014)
Carriers of mismatch repair (MMR) gene mutations have a high lifetime risk for colorectal and endometrial cancers, as well as other malignancies. As mutation analysis to detect these patients is expensive and time-consuming, clinical criteria and tumor-tissue analysis are widely used as pre-screening methods. The aim of our study was to evaluate the performance of commonly applied clinical criteria (the Amsterdam I and II Criteria, and the original and revised Bethesda Guidelines) and the results of tumor-tissue analysis in predicting MMR gene mutations. We analyzed 3,671 families from the German HNPCC Registry and divided them into nine mutually exclusive groups with different clinical criteria. A total of 680 families (18.5%) were found to have a pathogenic MMR gene mutation. Among all 1,284 families with microsatellite instability-high (MSI-H) colorectal cancer, the overall mutation detection rate was 53.0%. Mutation frequencies and their distribution between the four MMR genes differed significantly between clinical groups (p < 0.001). The highest frequencies were found in families fulfilling the Amsterdam Criteria (46.4%). Families with loss of MSH2 expression had higher mutation detection rates (69.5%) than families with loss of MLH1 expression (43.1%). MMR mutations were found significantly more often in families with at least one MSI-H small-bowel cancer (p < 0.001). No MMR mutations were found among patients under 40-years-old with only colorectal adenoma. Familial clustering of Lynch syndrome-related tumors, early age of onset, and familial occurrence of small-bowel cancer were clinically relevant predictors for Lynch syndrome.
Keywords: Adaptor Proteins, Signal Transducing/*genetics; Adenosine Triphosphatases/genetics; Adult; Aged; Colorectal Neoplasms, Hereditary Nonpolyposis/diagnosis/*genetics/pathology; DNA Mismatch Repair/genetics; DNA Mutational Analysis; DNA Repair Enzymes/genetics; DNA-Binding Proteins/genetics; Female; Germ-Line Mutation; Humans; Male; Microsatellite Instability; Middle Aged; Mismatch Repair Endonuclease PMS2; MutL Protein Homolog 1; MutS Homolog 2 Protein/*genetics; Nuclear Proteins/*genetics